La poesía en pugna: una lectura alternativa sobre el Ion de Platón (2020)
In the review of different studies made on Ion, it can be seen that this dialogue is read as an attempt by Plato to deny the value of poetry and rhapsody by stating that divine inspiration is incompatible with rational knowledge of the technique. The present investigation seeks to detach itself from such an understanding of the poetic and the rational and tries to show that, despite Plato's critical attitude towards poetry, he also recognizes in it certain peculiarities of its nature that are fundamental for philosophical inquiry. In the first chapter it is explained that in poetic discourse there is expression, but there is no explanation because of the lack of techne of the rhapsode. This does not mean, however, that technique is an ideal model of knowledge for Plato. The second chapter proposes that poetry, being the product of divine inspiration, constitutes a major good from which philosophy can be enriched...